Speech affordances: A structural take on how much we can do with our words. (23rd November 2016) - Ayala, Saray
Abstract: Individuals can do a broad variety of things with their words and enjoy different degrees of this capacity. What moderates this capacity? And in cases in which this capacity is unjustly disrupted, what is a good explanation for it? These are the questions I address here. I propose that speech capacity, understood as the capacity to do things with your words, is a structural property importantly dependent on individuals' position in a social structure. My account facilitates a non‐individualistic explanation of cases in which speech capacity is undermined due to speaker's perceived social identity, e.g. episodes of silencing. Instead of appealing to interlocutors' implicit bias against speaker's identity, a structural approach refers to the positions interlocutors occupy in the social structure and the discursive conventions operating upon those positions. I articulate my proposal drawing on the notion of affordances . Each position within a social structure is associated with its own range of speech affordances . Thus, speech capacity is a function of the probability distribution of speech affordances across positions in the structure.